The preparatory effects of problem solving versus problem posing on learning from instruction. (October 2015) - Kapur, Manu
Abstract: Two randomized-controlled studies compare the preparatory effects of problem-solving versus problem-posing on learning from subsequent instruction. Students engaged in either problem-solving (where they generated solutions to a novel problem) or problem-posing (where they generated problems, and where possible, the associated solutions) prior to learning a novel math concept. Study 1 found that problem-posing prior to instruction resulted in significantly better transfer to novel problems than problem-solving, without any significant difference in procedural knowledge and conceptual understanding. Study 2 further showed that when problem-posing was designed to focus only on the generation of problems without the solutions, problem-solving prior to instruction resulted in better conceptual understanding than problem-posing. However, the transfer effect remained in favor of problem-posing, albeit weaker than in Study 1. These findings suggest that although solution generation prior to instruction plays a critical role in the development of conceptual understanding and transfer, generating problems can further enhance transfer. Highlights: Problem-posing and problem-solving prepare differently to learn from instruction. Problem-posing results in better transfer of learning than problem-solving. Problem-posing results in equally good conceptual understanding as problem-solving. Problem-posing without solution generation diminishes conceptual understanding.